2016
DOI: 10.1038/tp.2015.220
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in dementia with Lewy bodies

Abstract: Dementia with Lewy bodies (DLB) is the second most common form of degenerative dementia. Siblings of affected individuals are at greater risk of developing DLB, but little is known about the underlying genetic basis of the disease. We set out to determine whether mutations in known highly penetrant neurodegenerative disease genes are found in patients with DLB. Whole-exome sequencing was performed on 91 neuropathologically confirmed cases of DLB, supplemented by independent APOE genotyping. Genetic variants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 26 publications
2
45
0
Order By: Relevance
“…In support of prior evidence (Keogh, et al, 2016; Tsuang, et al, 2013), the frequency of the APOE ε4 risk allele was significantly higher in our DLB cohort compared to Caucasian controls ( p -value < 0.001) and survival was significantly shorter in APOE ε4 carriers (Supplementary Figure 2). Interestingly, we found no pathogenic mutations in LRRK2, MAPT, PSEN2, SCARB2, and SNCA indicating that mutations in these genes are not a frequent cause of DLB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In support of prior evidence (Keogh, et al, 2016; Tsuang, et al, 2013), the frequency of the APOE ε4 risk allele was significantly higher in our DLB cohort compared to Caucasian controls ( p -value < 0.001) and survival was significantly shorter in APOE ε4 carriers (Supplementary Figure 2). Interestingly, we found no pathogenic mutations in LRRK2, MAPT, PSEN2, SCARB2, and SNCA indicating that mutations in these genes are not a frequent cause of DLB.…”
Section: Discussionsupporting
confidence: 91%
“…After completion of our analysis, a candidate gene study of exome data from a British DLB cohort was published (Keogh, et al, 2016). Similar to our findings, this study found an increased frequency of the APOE ε4 risk allele.…”
Section: Discussionmentioning
confidence: 99%
“…3 Third, even the largest cohorts of dementia with Lewy body samples have been generally small, in many instances including as few as 100 patients. 4,5 However, the fact that dementia with Lewy bodies has a strong genetic component is currently indisputable. The ε4 allele of APOE is recognised to be a strong risk factor, 6,7 as are heterozygous mutations and common polymorphisms in the glucocerebrosidase gene ( GBA ).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathological diagnosis of DLB is achieved when the presence of Lewy bodies is confirmed in the cortex and the brainstem (McKeith et al, 2005). Little is known about the genetics of DLB, although molecular studies seem to point toward genetic overlaps with other neurodegenerative diseases, mainly with AD and Parkinson’s disease (PD) (Bras et al, 2014; Guerreiro et al, 2016; Keogh et al, 2016; Meeus et al, 2012). …”
Section: Introductionmentioning
confidence: 99%